Assimilation, Acculturation, and Social Integration the Psychological Effect on Mixed Marriage in Sweden: Qualitative Study of Immigrants and Native Swedes - Olsson , Imaobong (Journal of Social Science Studies, 2023)
Assimilation, acculturation, and social Integration can have adverse psychological effects on marriage between immigrants and native Swedes. The study was conducted in Sweden. Immigrants in Sweden migrated from different countries and ethnic streams, many of which have different cultural norms and beliefs that may not fit well with the mainstream culture in Sweden. The method used in the study was the qualitative method with a semi-structured interview. Purposive and snowball sampling was used to locate the participants. Thus, this study aims to explore how assimilation, acculturation, and social Integration can psychologically affect mixed marriages between immigrants and native Swedes. Previously study focused on the positive assimilation of immigrants in the labor markets but not assimilation in marriage. Immigrants in Sweden have different families and social, cultural, and religious backgrounds with beliefs and norms that can be hard during the process of Integration, assimilation, and acculturation. The result indicated all the participants expressed positive and negative emotions that contributed to the conflict in their marriage during the assimilation, acculturation, and Social Integration process. These negative emotions of scary, worst pain, divorce sucks, gamophobia, bad, and subjection of children to the tragic scene, shameful thing influence mental health and is not a good thing. The results also indicate motivation, cultural beliefs, attitudes, and behavior after divorce. The finding will give awareness during the assimilation, acculturation, and social Integration; most immigrants may gradually lose all the markers, such as language, food, and customs.